2016
DOI: 10.1093/rheumatology/kew377
|View full text |Cite
|
Sign up to set email alerts
|

Both prolonged remission and Lupus Low Disease Activity State are associated with reduced damage accrual in systemic lupus erythematosus

Abstract: This cohort study shows that prolonged remission and LLDAS were associated with an improved outcome, as determined by yearly assessments. In order to improve the outcome in SLE patients, future studies should investigate whether these targets can be reached actively with therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
81
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(100 citation statements)
references
References 22 publications
6
81
0
4
Order By: Relevance
“…We demonstrated that prolonged remission, defined as 5 or more consecutive years of no clinical disease activity (SLEDAI-2K=0) in patients treated with antimalarials and/or stable dose of immunosuppressive drugs and/or prednisone ≤5 mg/day, was associated with a decrease in damage progression 10. This finding was confirmed by Tsang-A-Sjoe et al in a multiethnic cohort in the Netherlands 15. In a further study,11 we found that a remission lasting at least 2 years had still a protective effect against new damage.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…We demonstrated that prolonged remission, defined as 5 or more consecutive years of no clinical disease activity (SLEDAI-2K=0) in patients treated with antimalarials and/or stable dose of immunosuppressive drugs and/or prednisone ≤5 mg/day, was associated with a decrease in damage progression 10. This finding was confirmed by Tsang-A-Sjoe et al in a multiethnic cohort in the Netherlands 15. In a further study,11 we found that a remission lasting at least 2 years had still a protective effect against new damage.…”
Section: Discussionsupporting
confidence: 80%
“…In fact, the definition of LLDAS used in the study by Franklyn et al 12 Tsang-A-Sjoe et al 15 as well as in our study included patients who were in LDA but also patients in true remission. This is different from what was defined for RA and other rheumatic diseases,21 22 where the definitions of LDA and remission do not overlap (eg, disease activity score (DAS)-28 in RA identifies remitted patients when DAS-28 is lower than 2.6, while patients in LDA have a DAS-28 between 2.6 and 3.2).…”
Section: Discussionmentioning
confidence: 91%
“…In an Italian cohort, 7.1% of the patients achieved remission for at least 5 years11 whereas 12.8% did so in a Netherlands’ cohort12; 24% achieved remission for at least 1 year in a Spaniard cohort. Including PGA in the definition, 5.4% of LCTC patients were on remission for at least 1 year 5…”
Section: Discussionmentioning
confidence: 93%
“…Using this definition, a SLEDAI-2K score ≤4 is permitted (without any activity from the major organ systems), thus allowing for arthritis and myositis to be present. Likewise, a study by Tsang-A-Sjoe et al showed that LLDAS observed in ≥50% of observations (1 annual visit) was characterized by a 48% reduced risk of damage accrual as compared to patients with <50% time in LLDAS after 5 years (19). As such, it is questionable wheather a shortlived, partial remission (similar to the LLDAS) is clinically meaningful.…”
Section: Discussionmentioning
confidence: 99%